Avaliação de dor relacionada ao comportamento em professores da rede básica de ensino durante o ensino remoto emergencial - Alfaia, Fabiana de Alencar (Brasil, 2021)
The individual with acute or chronic pain has a characteristic of discomfort ranging from mild to agony, which can cause pain catastrophizing. In Brazil, the teaching profession is one of the most important and necessary, these professionals have a high level of stress, anxiety and incidence of pain. With the COVID-19 pandemic and the emergence of remote learning, these symptoms are expected to increase. The aim of this study is to evaluate and compare chronic pain, central sensitization and pain catastrophizing in primary school teachers during remote education due to the COVID-19 pandemic. 200 teachers from different regions of Brazil were recruited who answered, through an online form, a sociodemographic and working conditions questionnaire, the Central Sensitization Questionnaire (CSI) and the Catastrophic Thinking about Pain Scale (PCS) during the period of remote teaching. Most of the respondent teachers were female (77.5%), white (97%), residents of the Southeast region (89%), with lato sensu specialization (54%), had an income of 2 to 2.5 minimum wages. (15.5%), with a workload of 21 to 40 hours per week (57%). The main complaint of chronic pain was in the lumbar spine (mean 3.9). In the distribution of pain intensity, most teachers had chronic pain, especially in the lumbar spine region. Teachers who work more than 8 hours a day had more catastrophic thoughts than others. Teachers with salaries of R$3,000 to R$6,000 had a much higher level of pain than those who received higher salaries, as well as those who had difficulties with accessing the internet had greater pain awareness and catastrophizing.